Horses’ Use of Lying Halls and Time Budget in Relation to Available Lying Area - Linda Kjellberg (MDPI AG, 2021)
Sleep is crucial to horses’ wellbeing, and their lying time can vary according to such factors as climate, exercise, bedding, and housing. This study aimed to analyze behavior and time spent in lying halls of various sizes. We examined the influence of housing systems on total lying time and behavior, and how changes to available lying area can affect lying time. Two open barns were used in this study, with lying areas of 8, 15, and 18 m2/horse available in the lying halls. The horses’ behavior was video recorded and logged using scan sampling and interval observations. Individual boxes were used as a control. The horses were found to spend longer time in sternal and lateral recumbency in the hall with a lying area of 18 m2/horse than the hall with a lying area of 8 m2/horse. Increasing the area of the lying hall also increased overall time spent there. Consequently, the hypothesis that increasing lying area will increase the horses’ use of the lying hall, as well as their total lying time, was accepted.